(untitled) (REMUNOM, 2025)
This article aims to examine the requirements for eligibility and the grounds for ineligibility established by the 1988 Federal Constitution and related legislation, from the perspective of Constitutional Law and Electoral Law. The analysis is justified by the need to deepen the understanding of these requirements, providing greater clarity to the electorate and serving as a basis for future research in the field. The central issue consists of identifying the causes of ineligibility established in the 1988 Constitution. Although the constitutional text sets forth specific conditions for candidacy, legal doctrine presents divergences regarding the interpretation of certain provisions, which underscores the importance of this study. In this context, the research objectives were defined as follows: the general objective is to analyze the conditions of eligibility provided for in the 1988 Constitution; and the specific objectives are to compare doctrinal divergences concerning ineligibility, to conceptualize the legislation related to Constitutional Law, and to highlight the main requirements of eligibility and ineligibility. The investigation adopts a qualitative approach, based on a bibliographic review of an exploratory nature, which enabled the systematization of information and the formulation of relevant considerations. Finally, it was found that the right to vote constitutes one of the people’s greatest assets, representing the transfer of trust to the elected candidate, from whom governance guided by justice, ethics, and dignity is expected.